Role of microRNA alternation in the pathogenesis of gouty arthritis - Luo, Zhipan; Yang, Fan; Hong, Shaocheng; Wang, Jianpeng; Chen, Bangjie; Li, Liangyun; Yang, Junfa; Yao, Yan; Yang, Chenchen; Hu, Ying; Wang, Shuxian; Xu, Tao; et al. (Frontiers in Endocrinology, 2022)
Gouty arthritis is a common inflammatory disease. The condition is triggered by a disorder of uric acid metabolism, which causes urate deposition and gout flares. MicroRNAs are a class of conserved small non-coding RNAs that bind to the 3' untranslated region (UTR) of mRNA and regulate the expression of a variety of proteins at the post-transcriptional level. In recent years, attention has been focused on the role of miRNAs in various inflammatory diseases, including gouty arthritis. It is thought that miRNAs may regulate immune function and inflammatory responses, thereby influencing the onset and progression of the disease. This article mainly reviewed the roles of miRNAs in the pathogenesis of gouty arthritis and prospected their potential as diagnostic and prognostic relevant biomarkers and as possible therapeutic targets.